Pengaruh Teknik Slow Deep Breathing terhadap Penurunan Intensitas Nyeri pada Pasien Post Sectio Caesarea di Ruang Cempaka RSUD Dr. Doris Sylvanus Palangka Raya - Merry Delyka; Meilitha Carolina; Evie Evie (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Post-cesarean section women experience pain due to operative trauma. Pain sensation can be reduced by pain management. Pharmacological and non-pharmacological treatments can be used. The slow deep breathing technique is a non-pharmacological method suitable for reducing pain. But, they were always treated with analgesic medication and never did self-exercises such as slow deep breathing exercises to reduce the pain. Objective: To determine the effect of the slow deep breathing technique to reduce pain intensity in women after cesarean section in Cempaka Ward RSUD dr. Doris Sylvanus Palangka Raya. Method: Pre-Experimental research with one-group pre-test-post test design. The sampling technique is purposive, with 32 respondents based on inclusion and exclusion criteria. The data collection instrument uses a checklist, and data analysis uses the Wilcoxon test (p=0.05). Result: The result of the Wilcoxon statistic test is Sig. (2-tailed) 0.00 less than p=0.05, so H1 is accepted, which means there is the effect of a slow deep breathing technique to reduce pain intensity in women post-cesarean section. Conclusion: There is the effect of a slow deep breathing technique to reduce pain intensity in women post-cesarean section in Cempaka Ward RSUD dr. Doris Sylvanus Palangka Raya. Nurses or midwives must teach or even apply slow, deep breathing techniques to post-sectio caesaria women.